A comparative analysis on the effects of river discharge on trophic interactions in two tropical streams. Issue 1 (May 2017) - Weliange, Wasantha S.; Amarasinghe, Upali S.; Vijverberg, Jacobus; Leichtfried, Maria; Füreder, Leopold
Abstract : Discharge‐mediated seasonal patterns of food web interactions were investigated in two streams in Sri Lanka; Eswathu Oya (a perennial wet‐zone stream) and Yan Oya (a seasonal dry‐zone stream). Based on volumetric proportions of diet composition, relative abundance of fish species and their daily food rations, the mean cumulative consumption of each prey taxon was estimated for each fish population. Food web diagrams were prepared using trophic index of fish, trophic class of prey and feeding interactions between fish and prey. Both streams showed seasonal patterns of discharge due to rainfall, but no significant effect was evident in the trophic index of most fish species. In both streams, cumulative consumption of prey taxa was highest during low discharge regime due to increased abundance of both prey taxa and consumers. In Eswathu Oya, diversity of prey taxa was higher during the low discharge regime, but in Yan Oya, high diversity occurred during the high discharge regime. Herbivorous and/or detritivorous fish species were rare in Eswathu Oya but dominant in Yan Oya. Complex food web structure in Yan Oya due to high fish species richness and high diversity of prey categories made it less sensitive to discharge extremes in contrast to relatively simple food web structure in Eswathu Oya. This study, therefore, highlights the importance of maintaining the quality of riparian environments for conservation of biodiversity.